(untitled) (Theatrum historiae, 2015)
At the time of the Bohemian Estates Revolt in the year 1547, the Czech translation of a verdict from the year 1540, in which Emperor Charles V of Habsburg punished the present-day Belgian town of Ghent which had rejected the Emperor‘s tax demands, was published and disseminated in the press in Prague. Under the threat of a military attack, the citizens of Ghent decided to surrender to the Emperor, and expected negotiations about the payment of the monarchal financial demands to follow. However, having occupied the town with military force, Charles V seized all of the municipal property and handed down a harsh verdict with long-term consequences. This text was known in older Czech literature, but the circumstances and time of its origin were mistakenly assumed to be the very beginnings of the organized revolt in March 1547. On the basis of new research into the progress of the Estates Revolt, the author determines the origin of this material to be June 1547, i.e. the period after the Battle of Mühlberg, when most of the aristocratic part of the Bohemian Estates Revolt had reached an agreement with King Ferdinand, and the Bohemian royal towns remained the King‘s last potential opponents. The author compares the sanctions by King Ferdinand of Habsburg against the Bohemian royal towns (which, in 1547, had accepted the monarch‘s promises in good faith, just like Ghent) with the long-term anti-municipal policy of the Habsburgs, as well as with Emperor Charles V‘s actions in 1546 against Imperial towns that were members of the Schmalkaldic League.